Hospitalisation and Disease Severity Alter the Resting Pattern of Horses - Oliveira, Tiago; Santos, Amanda; Silva, Júlia; Trindade, Pedro [UNESP]; Yamada, Ana; Jaramillo, Fernando; Silva, Luis; Baccarin, Raquel (Elsevier, 2022)
In humans, hospitalisation, disease type, and environmental factors evidently affect the quality of sleep, further influencing patient recovery. The objective of the present study was to report the resting and lying behaviour of hospitalised horses, and whether lying behaviours differ depending on the physiological severity of joint damage. We hypothesised that the resting and lying behaviour can change during the hospitalisation and physiological severity of joint damage affect the time of rest in horses. A descriptive observational study was performed to evaluate the effect of hospitalisation on the recumbency time of 8 adult horses with different degrees of osteoarthritis of the metacarpophalangeal joint. The horses’ rest time was monitored using cameras during the first 5 days of hospitalisation. The total time of lateral recumbency and frequency of recumbency were greater after the 4th day of hospitalisation (P<,05), while the total time of sternal recumbency was greater after the 3rd day (P <0,05). Furthermore, we compared the recumbency time among animals with different degrees of osteoarthritis on the 5th day of hospitalisation. Increased recumbency time in mild osteoarthritis spared the animal's limb and reduced the overload on the affected limb; however, severe osteoarthritis decreased the frequency and time of recumbency probably due to greater difficulty during joint flexion in the transition from standing to recumbency. The severity of disease appeared to affect recumbency time, as horses with mild osteoarthritis spent more time in recumbency whilst those with severe osteoarthritis may have been partially sleep-deprived because they lay down less.
Keywords: Behaviour; Environmental factors; Equine; Osteoarthritis; Sleep